Teaching walks by "el jardín de las delicias" - Medina Domínguez, Javier; Robles Carrascosa, Ana (Avances en Supervisión Educativa, 2013)
The " «Paseos didácticos por el Jardín de las Delicias» are the result of experience gained with students from 1st ESO level to 2nd Bac level in which a work of art-The Garden of Earthly Delights by Hieronymus Bosch, has become the driving force of some of the work developed simultaneously and coordinately in the areas of Language Arts and Natural Sciences.All this exciting work ended collected on the web: http://arsvivendi.wix.com/040963. This work was awarded the Special Prize for the best work in the call XXVIII Awards Francisco Giner to improving educational quality. In addition the proposal was selected and presented in the Museo del Prado in the “II Encuentro” among teachers.